The Development of a Psychometrically Valid and Reliable Questionnaire to Assess Nutrition Knowledge Related to Pre-Schoolers - Rapson, Jeanette (Nutrients, 2020)
With rising childcare enrollments, caregivers have a unique opportunity to promote children’s nutrition education and healthy eating. Accurately identifying nutrition knowledge gaps amongst caregivers is necessary for professional development planning. Our aim was to design an early childhood education and care (ECEC) teacher nutrition knowledge questionnaire that satisfies psychometric criteria of validity and reliability. Items were based on the New Zealand Ministry of Health dietary guidelines, literature and expert advice. University students in their final year of a Bachelor of Science (BSc) in Human Nutrition (n = 40), and students with no nutrition background (n = 51) completed the questionnaire to assess construct validity; 35 BSc nutrition students completed the questionnaire two weeks later to assess reliability. The Mann-Whitney-U test and a median-split table assessed construct validity; Pearson’s product-moment correlation assessed test-retest reliability. Nutrition students achieved higher total and subcategory scores (p < 0.01). All nutrition students scored above the median of the combined group; 82% of non-nutrition students scored below the median. In testing reliability, first and second administration median scores for total and subcategories were significantly correlated (r = 0.43–0.78; p < 0.01). The questionnaire achieved construct validity and test-retest reliability and measured ECEC teachers’ nutrition knowledge for preschoolers.